2023
DOI: 10.1007/s10639-023-11582-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-pandemic pedagogy: Emergency remote teaching impact on students with functional diversity

Abstract: The Covid-19 outbreak caused transition from face-to-face teaching to Emergency Remote Teaching (ERT). Due to the hastily and disorganized implementation of ERT considerable difficulties were caused for all the students. Aim of the present study was to investigate (i) parents’ views of students with functional diversity regarding ERT during the Covid-19 pandemic and (ii) how their children’s functional diversity affected participation in ERT. ERT proved to be an even greater challenge for those students, who f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…They also had to consider how to provide equal learning opportunities for all the students, regardless of their internet access or device availability [19]. Additionally, as mentioned in previous research, parents of students with functional diversity reported that it was urgent to form an appropriate educational environment with specially designed educational material that meets the children's needs [20]. A study [21] showed that school directors had many roles during this shift, including planning for online teaching, starting online classes, using social media, managing the online program, helping everyone to adjust, and keeping everyone motivated.…”
Section: School Directors During Emergency Remote Teachingmentioning
confidence: 99%
“…They also had to consider how to provide equal learning opportunities for all the students, regardless of their internet access or device availability [19]. Additionally, as mentioned in previous research, parents of students with functional diversity reported that it was urgent to form an appropriate educational environment with specially designed educational material that meets the children's needs [20]. A study [21] showed that school directors had many roles during this shift, including planning for online teaching, starting online classes, using social media, managing the online program, helping everyone to adjust, and keeping everyone motivated.…”
Section: School Directors During Emergency Remote Teachingmentioning
confidence: 99%
“…Although the COVID-19 crisis completely transformed educational landscapes, it brought about new instructional practices and a new vision for the role of contemporary online education [12,13]. This promotes further research on instructional frameworks for online learning and ERT, which should be primarily based on pedagogical theories and psychology of learning and requires critical analysis and reflections on ongoing changes in educational systems, educational policies, and digital learning as a global approach to designing effective instructional systems of equal opportunities for all learners.…”
Section: Introductionmentioning
confidence: 99%